Gravity Signaling in Flowering Plant Roots - Su, Shih-Heng (Plants (Basel), 2020)
Roots typically grow downward into the soil where they anchor the plant and take up water and nutrients necessary for plant growth and development. While the primary roots usually grow vertically downward, laterals often follow a gravity set point angle that allows them to explore the surrounding environment. These responses can be modified by developmental and environmental cues. This review discusses the molecular mechanisms that govern root gravitropism in flowering plant roots. In this system, the primary site of gravity sensing within the root cap is physically separated from the site of curvature response at the elongation zone. Gravity sensing involves the sedimentation of starch-filled plastids (statoliths) within the columella cells of the root cap (the statocytes), which triggers a relocalization of plasma membrane-associated PIN auxin efflux facilitators to the lower side of the cell. This process is associated with the recruitment of RLD regulators of vesicular trafficking to the lower membrane by LAZY proteins. PIN relocalization leads to the formation of a lateral gradient of auxin across the root cap. Upon transmission to the elongation zone, this auxin gradient triggers a downward curvature. We review the molecular mechanisms that control this process in primary roots and discuss recent insights into the regulation of oblique growth in lateral roots and its impact on root-system architecture, soil exploration and plant adaptation to stressful environments.